Penggunaan Metode Bernyanyi Dalam Meningkatkan Kemampuan Mengenal Angka di KB Budi Mulia Kecamatan Galing - Betiana; Susilawati; Hadisa Putri (Tarbiya Islamica, 2023)
The research was conducted because it saw the phenomenon of a lack of ability to recognize numbers in young children, therefore teachers used the singing method. The approach taken to answer the problems in this research is qualitative, with descriptive methods. Researchers chose observation, interviews and documentation methods. To arrive at a conclusion, the data analysis that researchers use after data collection consists of: data reduction, data display, verification and drawing conclusions. Meanwhile, to check the validity of the data, continuous observation, data triangulation and member checking are used. The results of the research can be concluded: firstly designing the implementation of singing method learning, planning to improve learning ability to recognize numbers, learning carried out leads to achieving the singing method learning objectives, the final target of learning design planning, secondly planning learning must involve all learning variables, organizing learning, delivering learning, learning management, the learning that is created is determining the optimal learning method to achieve the goals that have been set and how to evaluate the singing method in improving the ability to recognize numbers, summarizing the singing method material, improving the ability to recognize numbers.